Pengembangan Media Busy Book untuk Meningkatkan Literasi Lingkungan pada Mata Pelajaran IPA Kelas V - Rahmawati Iswantary; Donna Boedi Maritasari; Abdul Aziz; Aswasulasikin Aswasulasikin (JURNAL PENDIDIKAN DASAR, 2023)
Abstract: This study aims to develop learning media in the form of Busy Books to improve students' environmental literacy in science subjects for class V. This study uses the ADDIE development model that has been developed by Robert Maribe Branch, which consists of five steps, namely analysis, design, development, implementation, evaluation. The results of media validation get results in the "good" category with a score of 40 (33.96 X 41.88), while the validation results from material experts get results in the "very good" category with a score of 47 (X 41.88), and finally the validation results from linguists got results in the "good" category with a score of 40 (33.96 X 41.88). While the results of small-scale trials obtained scores in the "agree" category with a score of 32.8 (27.18 X 33.54) and the results of large-scale trials scored in the "strongly agree" category with a score of 36.8 (X 33, 54). Based on these data, the media developed can be said to be feasible to use.Keywords: Media, Busy Book, Environmental Literacy  Abstrak:Penelitian ini bertujuan untuk mengembangkan media pembelajaran berupa Busy Book untuk meningkatkan literasi lingkungan siswa pada mata pelajaran IPA kelas V. Penelitian ini  menggunakan model pengembangan ADDIE yang telah dikembangkan oleh Robert Maribe Branch, yang terdiri dari lima langkah yaitu analisis, desain, pengembangan, implementasi, evaluasi. Hasil validasi media mendapatkan hasil dalam kategori “baik” dengan skor 40 (33,96 X ≤  41,88), sedangkan hasil validasi dari ahli materi mendapatkan hasil dalam kategori “sangat baik” dengan skor 47 (X 41,88), dan terakhir hasil validasi dari ahli bahasa mendapatkan hasil dalam kategori “baik” dengan skor 40 (33,96 X ≤  41,88). Sedangkan hasil uji coba skala kecil memperoleh skor dalam kategori “setuju” dengan skor 32,8 (27,18 X ≤  33.54) dan hasil uji coba skala besar skor dalam kategori “sangat setuju” dengan skor 36,8 ( X 33,54). Berdasarkan data tersebut, media yang dikembangkan dapat dikatakan layak untuk digunkan.Kata Kunci: Media, Busy Book,  Literasi Lingkungan